The New European Medical Device Regulation: Balancing Innovation and Patient Safety - Bretthauer, Michael; Gerke, Sara; Hassan, Cesare; Ahmad, Omer F; Mori, Yuichi (Annals of internal medicine, 2023)
The European Union has introduced stricter provisions for medical devices under the new Medical Device Regulation (MDR). The MDR increases requirements for clinical trial testing for many devices before they can legally be placed on the market and extends requirements for rigorous clinical surveillance of benefits and harms to the entire life cycle of devices. New "expert panels" have been established by the European Commission to advise in the assessment of devices toward certification, and the role of previous "notified bodies" (private companies charged by the Commission with ensuring that manufacturers follow the requirements for device testing) is being expanded. The MDR does not contain a grandfathering clause; thus, all existing medical devices must be recertified under the stricter regulation. The recertification deadline has recently been extended to 2027 or 2028, depending on the device's risk class. Whether most device manufacturers can meet these new requirements is uncertain, and the MDR will likely have important consequences for manufacturers, researchers, clinicians, and patients. Enhanced collaborations between the medical device industry and physician partners will be needed to meet the new requirements in a timely manner to avoid shortages of existing devices and to mitigate barriers to development of new devices.